Does chronic pain alter the normal interaction between cardiovascular and pain regulatory systems? Pain modulation in hypertensive-monoarthritic rat - Pinho, Dora (2011)
Hypertension-associated hypoalgesia is widely recognized in acute pain conditions. In chronic pain states, however, the relationship between blood pressure and pain sensitivity is still ill-defined, with different authors reporting negative, positive, or even no relationship at all. This work addresses this issue, using complete Freund's adjuvant (CFA)-induced monoarthritis in different models of hypertension: Spontaneous (spontaneously hypertensive rats, SHR), induced by infusion of angiotensin II (ANG) or 1,3-dipropyl-8-sulfophenylxanthine (DPSPX, an adenosine receptors' antagonist), and renal artery ligation (RAL). Nociceptive responses associated with monoarthritis were evaluated by different behavioral tests (von Frey, ankle-bend and CatWalk) and by quantification of Fos expression at the dorsal horn upon noxious stimulation. In all hypertension models, higher von Frey thresholds and lower Fos expression were detected in hypertensive rats with chronic inflammatory pain, as compared to normotensive monoarthritic rats. In SHR and DPSPX, but not ANG or RAL models, hypertensive animals displayed lower inflammation than normotensives. Ankle-bend and CatWalk results indicated lower pain sensitivity in hypertensive rats only in SHR and DPSPX models. The present study shows the importance of using multiple models of hypertension, and evaluating pain responses by various methods, to better understand the complexity of the interactions between pain and cardiovascular regulatory systems.